ANGELS Rating System for Islamic Banking Industry in Indonesia - Oktaviansyah, Hendrik Tri; Roziq, Ahmad; Sulistiyo, Agung Budi (Jurnal Keuangan dan Perbankan, 2018)
This study aims to analyze the bank soundness assessment usingÂ  ANGELS approach in an Islamic bank. This research is a qualitative research. This research uses a non-interactive qualitative approach that is an analysis research that conducts an assessment based on document analysis and provides interpretation of a concept. The data used are primary data and secondary data. Primary data is done by using structured interviews using prepared questionnaires. Secondary data from this research are sharia financial report year 2016 in the form of ROA, ROE, CAR, NPF, LDR, and MR. The results of this study indicate that the soundness assessment of Islamic bank using ANGELS has a score of 86.79 so it is said to be soundless. The concept of ANGELS which consists of Amanah Management, Non-Economic Wealth, Give Out, Earning, Capital and Asset, Liquidity and Sensitivity to Market and Economy Wealth in practice needs to be done revision is indicators Amanah Management of accountability to God and accountability to nature because in practice these indicators are contrary to the concept practiced in the field. Revision of accountability to God and accountability to nature is changed into ihsan and tablig.JEL Classification: G21; G24DOI:Â https://doi.org/10.26905/jkdp.v22i1.1563 Â